Lived experiences of exclusion in the workplace : psychological & behavioural effects - April, Kurt; Dharani, Babar; April, Amanda Ronita (Emerald Publishing Limited, 2023)
Exclusion is the process by which some people are out-grouped, or the state experienced by those alienated and/or marginalised. Lived Experiences of Exclusion in the Workplace shares the emotional expressions of those who have faced alienation and marginalisation -- from subtle to traumatic. Their stories reveal an abundance of factors which lead to exclusion and offer insights for the reader into instances of systemic-, organisational- and personal exclusion, as well as providing guidance on how to trigger belonging and inclusion through various, often simple measures. The presence of greater diversity in our organisations, as well as growing demands for equity, inclusion and social justice, compel us to address stumbling blocks. These findings collectively place remedial responsibilities in the hands of institutions, organisations, leaders, managers and employees who form the powerful/privileged in-group, as well as those who are excluded.
Keywords: Organizational sociology.; Diversity in the workplace.; Quality of work life.; Marginality, Social.; Business & Economics, Workplace Harassment & Discrimination.; Office & workplace.; elektronické knihy; electronic books